Ciência penitenciária no Brasil Império: disciplinar para construir a imagem da nação civilizada - Vasquez, Eliane Leal (2013)
In this research we have analyzed the Relatorio da Commissão Inspectora da Casa de Correcção da Corte (1874) written by Visconde de Jaguary, Antonio Nicoláo Tolentino, André Augusto de Padua Fleury, Luiz Bandeira de Gouvêa and José Augusto Nascentes Pinto. Analyzing the primary source was found that some of the ideas presented by the commissioners were results of the discussions of the International Penitentiary Congress of London (1872). It is manifest in report analyzed the presence of three proposals to reform the House of Correction of the Court: adoption of progressive classification of prisoners, essay of the theory of recompenses and review of the regulation of institution inspected. With relation the first proposal, the commissioners don‟t have cited the works of Sir. Walter Crofton to comment on the characteristics of progressive classification of prisoners, but written by Lucien Davesiés de Pontés or Mary Carpenter and others studies. In 1877, the report‟s proposals became known through publication entitled Transaction of the Fourth National Prison Reform Congress, that is, by an official document of the National Prison Association of the United States of America. The reference to the sources of prison literature of the nineteenth century evidenced the intellectual enterprise of commissioners to show that Brazil was informed about discussions the penitentiary science. In other words, revealed the interest of Emperor Dom Pedro II to know the functioning of prisons to discuss the organization of prison reform, when the prisons served of punitive spaces to establish the tranquility, order public and social control, and at the same time, to discipline human comportment. Therefore, the imperial elite‟s second reing used the debate about prison reform as discursive practice to build the image of civilized nation amid the local reality of slave society and to insert the name of Brazil in the prison reform movement